Prohibitory transactions of Sukuk assets: the shari'ah analysis with reference to Islamic capital markets - Adam Sa'ad, Auwal; Ansari, Abdul Haseeb (Serial Publication Private Limited India, 2018)
The paper discuses issues related to prohibitory transactions associated to Sukuk issuances in Islamic capital markets. The paper is elaborated based on the principles of prohibitory transactions such as gambling, riba (usury), gharar (excessive risk) non-halal products and services. The paper discussed issues related to future assets and services in which Islamic jurists have difference of opinion in accepting part of it as genuine Islamic assets for Sukuk transaction purposes. The paper also touches issues of the prohibitions and purification of income related to an Islamic financial institution. The paper suggests that rules related to Islamic contracts of sale such as bay’Muajjal, Murabahah, Salam, Istithna’, Ijarah should be strictly followed in any related sukuk issuance. Likewise partnership related contracts, such as Musharakah, Mudarabah, Wakalah and so on. It is also advised that Sukuk issuances must be strictly observing the Shari’ah principles of prohibitory transactions; couple with principle of purification of income where applicable.